(untitled) (Педагогіка вищої та середньої школи, 2010)
The article deals with the problem of using educational dialogue as a means of improvement pupils’ foreign communicative competence. The author gives definitions of such notions as "competence", "educational dialogue", "dialogical teaching ", and offers an example of the training for learning the main dialogical skills.